ANALISIS STRATEGI PENGEMBANGAN BISNIS PADA UMKM MENGGUNAKAN PENDEKATAN ANALISIS SWOT DAN QSPM MATRIKS - Moko, Wahdiyat; Dhara Dyah Wulandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The rapid growth of fashion has led to intense business competition in the fashion industry in Indonesia. The existence of intense competition with competitors requires business owners in the fashion industry to always pay attention to the needs and desires of consumers and understand their business to achieve competitive advantage in the midst of intense competition in the fashion business. The objective of this qualitative descriptive research is to identify the correct business development strategies for Cloura, an MSME engaged in fashion industry. Business competition in Indonesian fashion industry is one of the toughest competitions in the country. In order to win the competition and to gain competitive advantage, Cloura needs to have the appropriate business development strategies, which can be determined through analyses on IFE Matrix, EFE Matrix, SWOT, and QSPM Matrix. This study finds that the QSPM Matrix suggested final business development strategy, that is increasing market share for the existing products by conducting more intensive marketing campaigns.